A Jacobi-Collocation Method for Second Kind Volterra Integral Equations with a Smooth Kernel. (17th July 2014) - Guo, Hongfeng; Cai, Haotao; Zhang, Xin
Abstract : The purpose of this paper is to provide a Jacobi-collocation method for solving second kind Volterra integral equations with a smooth kernel. This method leads to a fully discrete integral operator. First, it is shown that the fully discrete integral operator is stable in bothL ∞ and weightedL 2 norms. Then, the proposed approach is proved to arrive at an optimal (the most possible) convergent order in both norms. One numerical example demonstrates the efficiency and accuracy of the proposed method.